Modeling of corn yield in Brazil as a function of meteorological conditions and technological level - Monteiro, José Eduardo Boffino de Almeida; Assad, Eduardo Delgado; Sentelhas, Paulo Cesar; Azevedo, Letícia da Costa (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to develop and evaluate a method for estimating corn yield using a minimum number of parameters and limited information about crop management. The proposed method estimates potential and attainable yields based on the technological level of the production systems and on relatively simple agrometeorological models. Corn yield was estimated for the crop seasons from 2000/2001 to 2007/2008, considering several locations and regions in Brazil, and was compared with the actual yield data from official surveys. There was a high correlation between the estimated and observed yield (0.76≤R2
Keywords: Zea mays; large-area crop modeling; paremetrization; risk analysis; technological potential yield; yield forecast